DINAMIKA KEBIJAKAN USAHA EKONOMI KELURAHAN SIMPAN PINJAM (UEK-SP) AIR HITAM GEMILANG KELURAHAN AIR HITAM KECAMATAN PAYUNG SEKAKI KOTA PEKANBARU DALAM PEMBERDAYAAN MASYARAKAT KELURAHAN TAHUN 2010-2018 - Wulan Ayu Widya Ningsih; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Community empowerment is a process in which the community, especially those who are resource-poor, neglected women and groups are supported in order to be able to improve their welfare independently. Increased independence and welfare of the community in this case through the development of potential, especially in terms of economic development. The development of the level of community welfare through the economic development policies of the urban community is then realized through the Savings and Loans Village Economic Business program (UEK-SP). The existence of this program is expected to improve the welfare of the community's life through the village economy through savings and loan activities. The formulation of the problem in this study is How is the interaction in the dynamics of the Savings and Loans Economic Business Policy (UEK-SP) black water resplendent black water village umbrella sekaki sub-district Pekanbaru city in the empowerment of urban community in 2010-2018 ?.This study aims to determine the form of interactions that occur in the dynamics of the Savings and Loans Economic Business Policy (UEK-SP) black water in the black water sub-village umbrella sekaki kota Pekanbaru in the process of community empowerment in 2010-2018. This research is a qualitative research with a descriptive approach. The research data obtained from observation, interviews and documentation.From the results of this research, it can be seen the interactions that occur in the dynamics of community empowerment policy through UEK-SP Air Hitam Gemilang include (1) interactions and interpretations between policies and internal organizations affected by the organization, (2) bureaucratic behavior from top to bottom, and (3 ) leadership behavior to members of the policy target group. Interactions that occur then cause changes in the organization organizing the UEK-SP program by the provincial government to the Pekanbaru city government through the Pekanbaru City Women's Empowerment and Family Planning Agency (BPPMKB).Keywords: Policy Dynamics, Community Empowerment, UEK-SP